A revista Veja e a construção da realidade dos evangélicos no Brasil: uma análise do discurso. - Santos, Eliana da Motta dos (2011)
The master´s degree dissertation. The Veja magazine and the construction of reality about evangelic people in Brazil: An analysis of speech , it´s not about judging as right or wrong the procedure of different religious chains of the Christian segment in Brazil or journalism that reports them, but also estimating how one of the most highly regarded periodical and read in the country mention facts and themes regarding to evangelic Christian segment, in its journalistic covering, participating in the social process of reality construction. In order to comprehend this process, the technique of analysis of speech was used, based on the qualitative method, in order to exploit, comprehend and find out the way that Veja magazine reports the religious segment. The corpus defined are the nine matters from the cover that show evangelic people throughout the 42 years of turnover (from 1968 to 2010) that´s 2197 issues of the Veja magazine. In order to establish a comparison to other Christian segments, the same issues that highlight the Roman Catholicism, were analyzed as well. The research is orientated by hypothesis that the speech contained in the reports builds a negative image of the evangelic people as an ironic tune and emphasizes situations implicate scandals and financial issues. This hypothesis also comprehends that journalists are not technical professionals devoid of imagination and vision about the world, in this case, an imaginary world towards religion, which is part of the news-construction that they partake. The theories of the imaginary world, especially with the theories of speech and the theories of journalism (production of news) are the base for the comprehension of the phenomenon and analysis of speech. We hope that this research contributes to make dialogue between religious society and professionals a bit easier, this way, contributing to a culture of peace and respect to the religious diversity and ideas in the Brazilian society, emphasizing ethical values of the professional of communication.